재활용 알루미늄 산화물을 이용한 수처리용 여재 제조방법 및 비소제거 - 이희용; 이남희; 김근한; 양재규; 박연종; 민경철; 이승목 (한국수처리학회지, 18(6), 2010)
In this study, the potential recycle of industrial wastes containing aluminum hydroxide generated during the sanding and sawing process in a local chemical company in Korea was evaluated. Aluminum oxide and gibbsite was prepared from the calcination of raw industrial waste containing aluminum hydroxide at different temperature. Four different filter media as a bead form were prepared at different ratio of alumina and gibbsite. Physicochemical properties of the prepared filter media were evaluated by FE-SEM analysis, compressive strength measurement and BET surface area analysis. As the ratio of gibbsite increased, compressive strength of filter media increased while the specific surface area was decreased. As(V) adsorption onto the filter media was followed a typical anionic type adsorption behavior. In this study, the potential recycle of industrial wastes containing aluminum hydroxide generated during the sanding and sawing process in a local chemical company in Korea was evaluated. Aluminum oxide and gibbsite was prepared from the calcination of raw industrial waste containing aluminum hydroxide at different temperature. Four different filter media as a bead form were prepared at different ratio of alumina and gibbsite. Physicochemical properties of the prepared filter media were evaluated by FE-SEM analysis, compressive strength measurement and BET surface area analysis. As the ratio of gibbsite increased, compressive strength of filter media increased while the specific surface area was decreased. As(V) adsorption onto the filter media was followed a typical anionic type adsorption behavior. KCI Citation Count: 3